Lives of a biologist : adventures in a century of extraordinary science - Bonner, John Tyler (Harvard University Press, 2002)
Annotation Beginning with the discovery of genes on chromosomes and culminating with the unmasking of the most minute genetic mysteries, the twentieth century saw astounding and unprecedented progress in the science of biology. In an illustrious career that spanned most of the century, biologist John Bonner witnessed many of these advances firsthand. Part autobiography, part history of the extraordinary transformation of biology in his time, Bonner's book is truly a life in science, the story of what it is to be a biologist observing the unfolding of the intricacies of life itself. Bonner's scientific interests are nearly as varied as the concerns of biology, ranging from animal culture to evolution, from life cycles to the development of slime molds. And the extraordinary cast of characters he introduces is equally diverse, among them Julian Huxley, J.B.S. Haldane, Leon Trotsky, and Evelyn Waugh. Writing with a charm and freshness that bring the most subtle nuances of science to life, he pursues these interests through the hundred years that gave us the discovery of embryonic induction; the interpretation of evolution in terms of changes in gene frequency in a population; growth in understanding of the biochemistry of the cell; the beginning of molecular genetics; remarkable insights into animal behavior; the emergence of sociobiology; and the simplification of ecological and evolutionary principles by means of mathematical models. In this panoramic view, we see both the sweep of world events and scientific progress and the animating details, the personal observations and experiences, of a career conducted in their midst. In Bonner's view, biology is essentially the study of life cycles. His book, marking the cycles of a life in biology, is a fitting reflection of this study, with its infinite, and infinitesimal, permutations.